Molten Salt Tritium Breeding Materials in Fusion Reactors: A Neutronic Comparative Analysis for ITER - Karakoç, Alper (New Energy Exploitation and Application, 2025)
This study investigates the effects of varying tritium breeding materials and their lithium enrichment rates on the Tritium Breeding Ratio (TBR) and Energy Multiplication Factor (M) within the tritium breeding zone of a fusion reactor. The magnetic fusion reactor model was developed based on the geometric and plasma parameters of the International Thermonuclear Experimental Reactor (ITER), ensuring a realistic representation of current fusion reactor designs. ITER‑grade stainless steel (SS 316 LN‑IG) was selected as the first wall material due to its excellent mechanical properties, high resistance to radiation damage, and compatibility with high‑temperature environments. The coolant and tritium breeding materials considered in the blanket included natural lithium, lithium fluoride (LiF), FLiBe (LiF‑BeF2), and FLiNaBe (LiF‑NaF‑BeF2). These materials were chosen for their ability to facilitate tritium breeding while maintaining thermal and neutronic efficiency. Neutron transport calculations and geometric modeling were performed using the widely recognized 3D simulation tools MCNP 5 and TopMC, which employ the continuous‑energy Monte Carlo method. The simulations utilized built‑in continuous‑energy nuclear and atomic data libraries, along with the Evaluated Nuclear Data File (ENDF) system (ENDF/B‑V and ENDF/B‑VI), ensuring reliable and validated results. The results highlight the importance of material selection and enrichment optimization in achieving efficient tritium breeding and energy production. FLiBe, in particular, shows promise for future fusion reactor designs due to its superior performance in terms of TBR and M. These findings provide valuable insights for the development of sustainable and high‑performance fusion reactors, contributing to the global pursuit of clean and virtually limitless energy.